IMPLEMENTASI AROMATERAPI PEPPERMINT UNTUK MENURUNKAN KEJADIAN POST OPERATIVE NAUSEA AND VOMITING PADA PASIEN DENGAN ANESTESI SPINAL: THE USE OF PEPPERMINT AROMATHERAPY TO REDUCE THE INCIDENCE OF POST-OPERATIVE NAUSEA AND VOMITING IN PATIENTS UNDERGOING SPINAL ANAESTHESIA - Hilda Nurul Janah (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
The prevalence of post-operative nausea and vomiting (PONV) after spinal anesthesia ranges from 27.7% to 59.3% worldwide. Both pharmaceutical and non-pharmacological treatments can be used to try to lower the incidence of PONV. Aromatherapy is one type of non-pharmacological treatment that can be used. Menthol (30–70%) and bioactive substances with spasmolytic and antiemetic effects, including as flavonoids, polyphenols, and tocopherols, are present in peppermint aromatherapy. This Community Service (PkM) initiative aims to evaluate the effectiveness of peppermint aromatherapy in treating post-spinal anesthesia pain. Thirty patients who satisfied the following requirements were included in the PkM method: they had to be undergoing elective or emergency spinal anesthesia, have a Gordon score of 0–3, be between the ages of 18 and 55, have a stable physical and mental state, be two to three hours post-surgery, and not have a peppermint allergy. The study was conducted at Gunung Jati General Hospital in Cirebon from November 5–12, 2025. It started with an educational session about PONV and the advantages of peppermint aromatherapy. After that, 5–10 drops of peppermint essential oil were added to a diffuser filled with water to deliver peppermint aromatherapy for 15 minutes. The Gordon score was used for the PONV evaluation both before and after the intervention. According to the Community Service (PkM) activity's outcomes, 36.7% of patients had a score of 1 before the intervention, while 63.3% had a score of 0. The percentage of patients with a score of 0 rose to 90.0% after receiving peppermint aromatherapy, while the percentage with a score of 1 dropped to 10.0%. Peppermint aromatherapy can be utilized to prevent and lower the incidence of PONV in patients after spinal anesthesia, according to the findings of this community service project.. The outputs of this community service activity include a pocket guide and a published article on community service.